2017
DOI: 10.3390/su9081340
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Environmental and Health Claims on New Legume Products: A Non-Hypothetical Online Auction

Abstract: Legumes are valued in agricultural systems, as they can contribute to a more sustainable land use. However, their economic value is low. Despite health and environmental benefits, marketers struggle to communicate the worth of legumes to consumers. We evaluate the worth of health and, in particular, environmental claims that would spread consumers' awareness of ecological advantages. Utilizing a large consumer sample, we execute binding online auctions. Comparing claim-treated and untreated subjects (between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 43 publications
(87 reference statements)
0
37
0
Order By: Relevance
“…Combination labelling received consistently high WTP. One study calculated WTP for a mix of nutrition-health and environmental attribute information, with this resulting in a WTP premium of 35%, the highest marginal effect within the study [49]. A similar result can be seen in Bond [63], where combining an organic claim with one for vitamin C led to an 18% price premium compared to 3.7% and 7.4% for the respective label claims in isolation.…”
Section: Willingness-to-pay For Attribute Informationmentioning
confidence: 53%
See 3 more Smart Citations
“…Combination labelling received consistently high WTP. One study calculated WTP for a mix of nutrition-health and environmental attribute information, with this resulting in a WTP premium of 35%, the highest marginal effect within the study [49]. A similar result can be seen in Bond [63], where combining an organic claim with one for vitamin C led to an 18% price premium compared to 3.7% and 7.4% for the respective label claims in isolation.…”
Section: Willingness-to-pay For Attribute Informationmentioning
confidence: 53%
“…Nine studies showed a preference for nutrition or nutrition-health label information; one study finding no significant difference between descriptive labels but with a trend toward the nutrition-health label. Three studies found a mix of both health and environmental and/or social responsibility attributes were most popular [47,49,50]. In those studies where environmental and social responsibility attributes were preferred, organic was the preferred choice in eight studies [28,43,46,[51][52][53][54], with animal welfare claims coming a close second (five studies) [44,[55][56][57][58].…”
Section: Attribute Preferencementioning
confidence: 99%
See 2 more Smart Citations
“…If both the claims "reduced-fat" and "low salt" were presented on the same package consumers were willing to pay a premium price. Lemken (2017) [28] also observed differences in consumers' WTP for diverse types of nutrition claims conveyed on legumes pasta. He found that legume pasta advertised with nutrition claims showed a higher WTP than conventional pasta and in particular the fibre claim appeared to be superior to that of the protein claim.…”
Section: Introductionmentioning
confidence: 96%